HUBUNGAN KOORDINASI MATA-TANGAN DENGAN KETEPATAN SERVICE FOREHAND TOPSPIN TENIS MEJA PUTRA PTM MALAY PEKANBARU - Lestari, Ivana; ', Ramadi; Juita, Ardiah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Based on the observations of researchers at table tennis team PTM Malay Pekanbaru, that the precision in forehand topspin service is still weak, it can be seen from several matches and in training. This could be seen where the ball was stuck in the net, out of the field even with opponents easily restore service forehand topspin by the opponent. This research aims to look at the correlation of eye-hand coordination for the accuracy service forehand topspin male table tennis of PTM MALAY Pekanbaru. The population in this study is the male table tennis team with total 10 people. Considering the little amount of the population, the entire of them are to be sampled (total sampling). Thus, the sample in this study is the male team table tennis PTM MALAY as much as 10 people. The test is used to measure the eye and hand coordination is to catch a tennis ball with the throwing test and to measure the skills of table tennis serve, is to test the service. The obtained data were analyzed by Pearson Product Moment. Based on the results of research that has been described in the previous chapter, it can be concluded that the results obtained from hand-eye coordination had no correlation with the precision of service in forehand topspin of male table tennis of PTM MALAY Pekanbaru. This could be seen from the results and data analysis stated rhitung <rtabel, so it can be concluded that there is no correlation between the variables.  Key Words: Coordination of Eye and Hand, Accuracy forehand topspin serve